2022
DOI: 10.1002/14651858.cd007039.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for perceptual disorders following stroke

Abstract: Background Perception is the ability to understand information from our senses. It allows us to experience and meaningfully interact with our environment. A stroke may impair perception in up to 70% of stroke survivors, leading to distress, increased dependence on others, and poorer quality of life. Interventions to address perceptual disorders may include assessment and screening, rehabilitation, non‐invasive brain stimulation, pharmacological and surgical approaches. Objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 114 publications
1
1
0
Order By: Relevance
“…This is consistent with findings in previous studies, which showed that 33 to 61% return to driving after a stroke (Aufman et al, 2013;Perrier et al, 2010;Venketasubramanian & Chan, 2023). Our simple measure of arm use explained 34% of the variability in return to driving, which is large given that various impairments that present in stroke such as motor, visual, cognitive, perceptual, and sensory deficits can affect the ability to drive (Akinwuntan et al, 2012;Bolognini et al, 2016;Hazelton et al, 2022). It is possible that stroke survivors who return to driving have better arm function or less disability, which can translate into more social activities (Aufman et al, 2013;Legh-Smith et al, 1986;Schnitzler et al, 2019), which contributed to the greater participation that we observed.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with findings in previous studies, which showed that 33 to 61% return to driving after a stroke (Aufman et al, 2013;Perrier et al, 2010;Venketasubramanian & Chan, 2023). Our simple measure of arm use explained 34% of the variability in return to driving, which is large given that various impairments that present in stroke such as motor, visual, cognitive, perceptual, and sensory deficits can affect the ability to drive (Akinwuntan et al, 2012;Bolognini et al, 2016;Hazelton et al, 2022). It is possible that stroke survivors who return to driving have better arm function or less disability, which can translate into more social activities (Aufman et al, 2013;Legh-Smith et al, 1986;Schnitzler et al, 2019), which contributed to the greater participation that we observed.…”
Section: Discussionsupporting
confidence: 91%
“…This Cochrane review update and expansion assessed the effectiveness of interventions for perceptual disorders after stroke. 1…”
mentioning
confidence: 99%